(untitled) (Jurnal Manajemen dan Kewirausahaan, 2005)
This reseach briefly explains to what extent customer satisfaction has significant influence to the customer loyalty of ’Iklan Jitu’ Jawa Pos newspaper in Sarana Media Advertising. Moreover, it also explores variable that give the biggest contribution to the customer loyalty. Four variables are using as customer satisfaction representatives, which are reliability, response to and remedy of problems, sales experience and convenience of acquisition. Finally, the findings shows that sales experience is the biggest contributor to the customer loyalties. Abstract in Bahasa Indonesia : Penelitian ini dimaksudkan untuk mengetahui sejauh mana kepuasan pelanggan mempunyai pengaruh signifikan terhadap loyalitas pelanggan Iklan Jitu surat kabar Jawa Pos pada CV.Sarana Media Advertiseng dan variabel mana yang memberikan kontribusi terbesar pengaruhnya terhadap loyalitas pelanggan. Dalam penelitian ini mengunakan empat variabel untuk mewakili keppuasan pelanggan yang meliputi : reliability,response to and remedy of problems, sales experience dan convenience of acquisition. Dari hasil perhitungan diketahui bahwa sales experience memberikan kontribusi terbesar terhadap loyalitas pelanggan. Kata kunci : kepuasan pelanggan, loyaliras pelanggan.